Asian Critical Theory and Counternarratives of Asian American Art Educators in U.S. Higher Education. (2nd October 2022) - Shin, Ryan; Bae, Jaehan; Gu, Min; Hsieh, Kevin; Koo, Ahran; Lee, Oksun; Lim, Maria
Abstract : This article is a collective counternarrative of seven Asian American art educators in higher education in the United States. Critically reflecting on their research and pedagogical practices, we attempt to recognize and address the voices and challenges of Asian Americans in the field of art education. We employed Asian Critical Theory as a theoretical framework, combined with collaborative autoethnography as a research methodology. Confronting racial stereotypes and discrimination against Asian Americans, we underlined the voices of Asian American art educators whose linguistic and cultural values are in stark contrast with those of mainstream American art educators. After reflecting on our shared stories and experiences, we suggest a new pedagogical approach, "Asian Critical Pedagogy, " to redress and transform our experiences to attain the broader goal of racial and social justice in the field of art education.